Analisis Keterampilan Penggunaan Alat Ukur terhadap Pemahaman Konsep pada Materi Besaran dan Satuan - Mila Rosa Angraini; Suprianto, Suprianto; Nur Fadilah; Yasmin Sabrina Nur Islami; Mubayyinah Muliyadi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the correlation between skills in using measuring instruments and understanding the concept of quantities and units in semester 1 students of the Physics Education study program at Madura Islamic University. The research method used is a quantitative approach with a pre-experimental approach. The sample in this research involved semester 1 students of the Madura Islamic University physics education study program who were taking basic physics 1 courses. Data collected in this research was through the distribution of essays regarding understanding the concept of quantities and units (Y) as well as skills in using measuring instruments (X ) with certain indicators. The values obtained from this research were analyzed using the SPSS statistical application with linear regression tests and correlation tests. The results of data analysis show that the correlation value = -0.384 with a significant value = 0.244 and Rsquare = 0.147. Based on the data analysis, it can be concluded that there is a negative correlation and does not have a significant impact on skills in using measuring instruments on understanding the concept of quantities and units. Skills in using measuring instruments contribute 14.7% to understanding the concept of quantities and units, while 85.3% is influenced by other factors.